O papel do Fundo de Financiamento Estudantil (FIES) na reconfiguração do ensino superior do Estado da Paraíba (1999 – 2018) - Silva, Alexandre Nascimento da (2020)
The present objective research aims to analyze public policies for financing private higher education and its implications in the process of reconfiguring higher education in the State of Paraíba, from 1999 to 2018. As a starting point, account was taken of the openness and non-regulation of the educational market alluding to private higher education and the commercialization of educational relations. In fact, it seems that the most visible side of these financing policies accentuates the commercialization of scientific knowledge, based on guidelines from international organizations. To this end, a rigorous study of the expansion and financing programs was carried out, more specifically the Student Financing Fund (FIES), seeking to apprehend the origins, changes, functioning and financial sustainability of the program. Based on official information regarding financial resources, enrollment, dropout, it was possible to advance in the understanding of the role of FIES in the reconfiguration of higher education in the State of Paraíba, the locus of the study. For this investigation, it was decided to develop a of character predominantly qualitative research, based on bibliographic and documentary research, as well as incorporating quantitative analysis, involving statistical correlation measures. The analysis and discussion of the data demonstrated that there was: a significant process of expansion of higher education in the analyzed period, with a strong induction of private enrollments and consequent commercialization of teaching; the decentralization of private institutions by several micro-regions of the State and the entry of large educational groups, with the incorporation of local institutions, indicating progress in the oligopolization of higher education in Paraíba. Finally, it was revealed that, in relation to the increase in public funding, dropout rates in private education cast doubt on the quality of the offer of places in this segment.